Bridging Behavioral Models and Theoretical Concepts: Effectuation and Bricolage in the Opportunity Creation Framework. (March 2016) - Welter, Chris; Mauer, René; Wuebker, Robert J.
Abstract : Research summary: Opportunity creation, effectuation, and bricolage are three concepts that describe value creation and the central role of entrepreneurial action in that process. Although research often conceptualizes these concepts as interrelated, precisely how they relate to and complement one another and where they diverge remains unclear. This article examines the roots of each of these concepts and their underlying assumptions, organizing them within a unifying conceptual frame. Our analysis reveals a set of entailing implications that can guide future conceptual and empirical work in entrepreneurship, and it advances our understanding of value creation and capture in strategy, organization theory, management, and related fields. Managerial summary: What are entrepreneurs doing? At the highest level of abstraction, entrepreneurs are identifying and exploiting opportunities. Recently, several lines of research have examined how certain types of entrepreneurial action can result in forming, rather than merely encountering, opportunities. Scholars engaged in this work have used both deductive and observational approaches, which have been rarely examined jointly or integrated into a comprehensive framework. This article focuses on the literature on opportunity creation, effectuation, and bricolage, examining each of the approaches and their underlying assumptions, and it organizes them within a unifying conceptual frame. Doing so reveals avenues for future work, in particular the development of new theories of opportunity formation, and implications for research in related fields such as strategic management, organization theory, and economics. Copyright © 2016 Strategic Management Society.